PENGEMBANGAN LKPD BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN IPS KELAS V SD NEGERI 32 LUBUKLINGGAU - Tata Novela, Rudi Erwandi; Dedy Firduansyah, Dea Iintri Oktriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop a LKPD media design based on local wisdom in social studies learning. Testing the validity, practicality and effectiveness of local wisdom-based LKPD media in social studies learning for fifth grade students at SDN 32 Lubuklinggau. This type of research is Research and Development with the ADDIE development model. The subjects of this research were class V students at SDN 32 Lubuklinggau. Data collection techniques use observation, interviews, questionnaires and tests. Based on the results of the validity analysis of local wisdom-based LKPD media in social studies learning using Aiken's V, the language validator's assessment was 0.89, the media validator was 0.89 and the material validator was 0.92. Analysis of teacher and student practicality sheet assessments showed that local wisdom-based LKPD media in social studies learning met the very practical criteria with an average score of 90.08%. Then analysis of the effectiveness assessment obtained an average N-Gain score of 0.73 in the high category. Based on the research results, it can be concluded that local wisdom-based LKPD media in social studies learning has proven to be valid, practical and effective so it is suitable for use in the fifth grade learning process at SDN 32 Lubuklinggau.